Doença do refluxo gastroesofágico e erosões dentárias : influência do consumo de alimentos acidificados e impacto na qualidade de vida - Milani, Daiane Cristina (2015)
Gastroesophageal reflux disease (GERD) has an established association with dental erosions (DE). However, extrinsic factors such as acidified foods also might contribute to the development of DE. The objective this study was assessed whether GERD is associated with DE controlling for acidified food intake, and their relationships with quality of life. In this cross-sectional study, 419 adult patients who seek dentistry consultation were considered eligible. Patients replied to questionnaires for evaluation of GERD symptoms, acidified food ingestion and general quality of life, followed by oral examination, in which DE were characterized according to Smith & Knight criteria. The statistical analysis was performed using the Mann-Whitney, Chi-square, Poisson regression and Kruskal-Wallis tests. A total of 417 patients were included (aging 43.8 ± 13.7 yr; 68.8% women). There were 143 patients with GERD (34.3%) and 274 controls without GERD. The prevalence of DE was higher in GERD patients as compared to controls (25.9% vs. 17.2%; P = 0.041). GERD was associated with DE after adjusting for acidified food intake (P = 0.035). The inclusion of age and sex in the model had no effect on this association. Quality of life decreased two points on average in the presence of GERD, regardless of DE. In adult patients examined in a dentistry center in University of Passo Fundo, dental erosions were prevalent and significantly associated with GERD. Such association was independent of the intake of acidified food. The negative impact on general quality of life was dependent of GERD, regardless of the presence of dental erosions